2006
DOI: 10.1136/jnnp.2006.106690
|View full text |Cite
|
Sign up to set email alerts
|

Progression of non-age-related callosal brain atrophy in multiple sclerosis: a 9-year longitudinal MRI study representing four decades of disease development

Abstract: Background: In multiple sclerosis (MS), multiple periventricular lesions are commonly the first findings on MRI. However, most of these MS lesions are clinically silent. The brain atrophy rate has shown better correlation to physical disability, but it is not clear how atrophy develops over decades. Corpus callosum forms the roof of the third and lateral ventricles. The corpus callosum area (CCA) in a midsagittal image is age independent in a normal adult population up to the seventh decade; therefore it can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…MRI studies have confirmed that CC atrophy is a common finding in MS [4951], and histopathologic studies indicate early axonal injury, transection of axons passing through the CC and Wallerian degeneration over time [41,52]. As with mouse experiments during the chronic demyelinating state, current DTI studies in progressive MS patients with longer disease duration (over 3 years) did not demonstrate decreased λ || .…”
Section: Cns Demyelination: Msmentioning
confidence: 84%
“…MRI studies have confirmed that CC atrophy is a common finding in MS [4951], and histopathologic studies indicate early axonal injury, transection of axons passing through the CC and Wallerian degeneration over time [41,52]. As with mouse experiments during the chronic demyelinating state, current DTI studies in progressive MS patients with longer disease duration (over 3 years) did not demonstrate decreased λ || .…”
Section: Cns Demyelination: Msmentioning
confidence: 84%
“…The EDSS correlation results imply that brain atrophy and the NAWM burden of disease are better predictors of disability. It is known from previous studies that brain atrophy (PVF) correlates with EDSS, although the strength of this correlation has ranged from weak to moderate (Furby et al, 2008; Kalkers et al, 2002; Martola et al, 2007, 2010; Rudick et al, 2009). However, our work is the first to show that a quantitative myelin water fraction measure derived from mcDESPOT acquisition adds statistically significant patient disability predictive value on top of PVF, as evidenced by its inclusion in the optimal multiple linear regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ALS, MRI parameters provide also valuable information regarding the process of neurodegeneration in MS. Whole brain atrophy was consistent in all MS patients but with different rates according to clinical phenotypes ranging from 0.5%–0.8% in RRMS to 1.3%–1.4% in SPMS and 1%–1.3% in PPMS [ 12 ]. However, other studies showed differences between rates of grey matter atrophy (GMA) and white matter atrophy (WMA) with a relative constant WMA rates (about three-fold the normal) in CIS, RRMS and PMS patients and a much more aggressive GMA in SPMS patients (about 14-fold) when compared to CIS patients (three or four-fold) [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPMS and ALS, although two different etiologic entities, share some common pathophysiological pathways involving axonal death, apoptosis, and gliosis occurring already in preclinical stages. Degeneration of the long tracts in the spinal cord with clinical signs of upper motor neurons (UMN) occur in PPMS patients [ 11 ] as well as in ALS [ 7 ] associated with progressive spinal cord atrophy in both diseases [ 12 , 13 ]. Moreover, other diseases involving the long tracts of the spinal cord like hereditary spastic paraplegia (HSP) and primary laterals sclerosis (PLS) share similar clinical features with PPMS and classical ALS [ 14 , 15 ] and may challenge differential diagnosis [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%